(untitled) (Üçüncü Sektör Sosyal Ekonomi Dergisi, 2026)
This study aimed to examine the relationship between social dominance orientation (SDO), emotional appetite, and eating attitudes among political party members during the election period, which is characterized by increased psychosocial stress and changes in daily routines. A total of 631 participants (mean age 34.02±12.73 years) completed the Social Dominance Orientation Scale (SDO7), Emotional Appetite Questionnaire (EMAQ), and Eating Attitudes Test (EAT-26) through face-to-face interviews. The findings revealed that individuals with higher SDO scores exhibited lower emotional appetite and reduced “eating preoccupation” in negative emotional situations (p<0.01). Additionally, when the “anti-egalitarianism” sub-factor of SDO increased by one unit, emotional appetite decreased by 0.800 times in negative situations, while it increased by 0.350 times in positive situations (p<0.001). Furthermore, a one-unit increase in this sub-factor was associated with a 0.259 times decrease in eating disorder behaviors (p<0.001). Overall, the results suggest that social dominance orientation plays a significant role in shaping individuals’ eating behaviors by influencing both emotional appetite and eating attitudes, particularly under stress-related conditions such as election periods, and may contribute to more controlled eating patterns in certain contexts.